Barriers and enablers to using evidence-based antibiotic prescription guidelines in primary care: a qualitative systematic review and synthesis using the theoretical domains framework - Bursey, Krystal; Patey, Andrea M.; Etchegary, Holly; Aubrey-Bassler, Kris; Kavanagh, Victoria; Pike, Andrea; Romme, Kristen; Grimshaw, Jeremy M.; Hall, Amanda (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background Antibiotics are commonly overprescribed for upper respiratory tract infections (URTIs) in primary care against widely known guideline recommendations. To design an effective intervention to improve adherence to URTI guideline-based care, it is important to understand why the behaviour persists. This review aimed to conduct a qualitative systematic review of the barriers and enablers to URTI guideline-based prescribing for FPs in primary care using a Theoretical Domains Framework (TDF)-based analysis. Methods The following databases were searched with no date or language restrictions from inception to December 2024: MEDLINE, Web of Science, CINAHL, Embase, The Cochrane Library, and APA PsycInfo. Qualitative studies that explored FP’s experiences with following antibiotic prescription guidelines for URTIs were included. Data on the barriers and enablers for URTI guideline adherence were extracted and analyzed using the TDF approach and categorized into the 14 TDF domains. Barriers and enablers were assessed for confidence using the Grading of Recommendations Assessment, Development and Evaluation—Confidence in the Evidence from Reviews of Qualitative Research (GRADE-CERQual) approach. Results A total of 2837 articles were screened, and 23 studies were included. The included studies had moderate to high methodological rigour and included a total of 516 FPs. A total of 61 barriers across 13 TDF domains were identified but only 17 barriers across 8 TDF domains were determined to have high confidence. These barriers with high confidence largely centered on (1) lack of support for guideline-based prescribing and physician fatigue, (2) perception of patient demand for antibiotics and the doctor-patient relationship, and (3) poor physician understanding of antibiotic resistance and antibiotics and their role in patient care. A total of 40 enablers across 13 TDF domains were identified but only 10 enablers across 8 TDF domains were judged to have high confidence. The enablers with high confidence were related to (1) knowledge of the impact of antibiotic use on antibiotic resistance and prioritizing evidence-based care, and (2) antibiotic reduction strategies for both physician and patient. Conclusion This review found 17 barriers to adhering to URTI antibiotic prescribing guidelines for FPs in primary care across 8 TDF domains. This is important because many interventions do not target all the TDF domains we identified as barriers. Future intervention design should consider adopting strategies to target these domains to ensure its efficacy in improving guidelines adherence.